Pelatihan Public Speaking dan Pengasahan Rasa Percaya Diri - Firda Aulia; Inna firdan Choirun Habibah; Nur Hayati Amalia; Moch. Falihul Hilmi; Moch. Andi Maulana Islam; Miftahul Abdul Lathif; Subekti, Mohammad Yusuf Agung (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract The Muhadharah activity is an effort to foster the self-confidence of santri However, santri often lack self-confidence when they are going to appear in the activity. The purpose of this service is to try to increase the santri' self-confidence in showing themselves in public. This service was carried out at the Hidayatul Mubtadiin Singosari Islamic Boarding School in November-December 2023 with the target of the service being the administrators and santri who are assigned to the muhadharah activity. The results of the service show that the muhadharah activity which is carried out once a week on Friday night after the Isha prayer is very important for training the courage and self-confidence of santri with tasks including being the host, khatib/khatibah, qori'/qori'ah, istimbat, entertainment, and commentator. Before appearing, students are given one week to create a speech text and prepare everything needed when appearing in the muhadharah activity. To build the self-confidence of the santri, what needs to be considered is a sense of love, a sense of security, role models, knowledge, and relationships. The administrator at the end of the activity delivers directions or evaluations of the activity, for students who are not responsible for their duties will be given a warning and must be accountable for it in the following month. Keywords: Muhadharah, Public Speaking, Santri. Abstrak Kegiatan Muhadharah merupakan upaya untuk menumbuhkan percaya diri Santri. Namun, sering kali para santri kurang percaya diri saat akan tampil dalam kegiatan tersebut. Tujuan dari pengabdian ini untuk mengupayakan peningkatan rasa percaya diri santri dalam unjuk diri di depan umum. Pengabdian ini dilaksanakan di Pondok Pesantren Hidayatul Mubtadi’in Singosari pada bulan November-Desember 2023 dengan sasaran pengabdian adalah pengurus dan santri yang bertugas pada kegiatan muhadharah. Hasil pengbadian menunjukkan bahwa kegiatan muhadharah yang dilaksanakan setiap seminggu sekali pada malam Jum’at setelah salat isya’ sangat penting untuk melatih keberanian dan rasa peracaya diri santri dengan tugas di antaranya menjadi pembawa acara, khatib/khatibah, qori’/qori’ah, istimbat, hiburan, dan komentator. Sebelum tampil santri diberi waktu satu minggu untuk membuat teks pidato dan mempersiapkan segala sesuatu yang dibutuhkan saat tampil dalam kegiatan muhadharah. Untuk membentuk kepercayaan diri santri yang perlu diperhatikan adalah rasa cinta, rasa aman, model peran, berpengetahuan, dan hubungan. Pengurus di akhir kegiatan menyampaikan arahan atau evaluasi dari kegiatan tersebut, bagi santri yang tidak bertanggung jawab dengan tugasnya akan diberikan teguran serta harus mempertanggung jawabkannya di bulan berikutnya. Kata kunci: Muhadharah, Public Speaking, Santri.